Anti-parasitic egg rejection by great reed warblers (Acrocephalus arundinaceus) tracks differences along an eggshell color gradient - Abolins-Abols, Mikus; Hanley, Daniel; Moskát, Csaba; Grim, Tomáš; Hauber, Mark E (Behavioural processes, 2019)
One of the most effective defenses against avian brood parasitism is the rejection of the foreign egg from the host's nest. Until recently, most studies have tested whether hosts discriminate between own and foreign eggs based on the absolute differences in avian-perceivable eggshell coloration and maculation. However, recent studies suggest that hosts may instead contrast egg appearances across a directional eggshell color gradient. We assessed which discrimination rule best explained egg rejection by great reed warblers Acrocephalus arundinaceus, a frequent host to an egg-mimetic race of common cuckoos Cuculus canorus. We deployed 3D-printed model eggs varying in blue-green to brown coloration and in the presence of maculation. Using visual modeling, we calculated the absolute chromatic and achromatic just-noticeable differences (JNDs), as well as directional JNDs across a blue-green to brown egg color gradient, between host and model eggs. While most model eggs were rejected by great reed warblers, browner eggs were rejected with higher probability than more blue-green eggs, and the rejection probability did not depend on maculation. Directional egg color discrimination shown here and in a suite of recent studies on other host species may shape the cognitive decision rules that hosts use to recognize foreign eggs and affect the course of evolution in parasitic egg mimicry.
Keywords: Passeriformes; Color Perception; Nesting Behavior; Maculation; Perception; Color; Defense; zvířata; Egg Shell; hnízdění; barva; Brood parasitism; Metareplication; JND; vnímání barev; vaječná skořápka; Animals